CRP monitoring in fractured neck of femur. A waste of resource?. Issue 10 (October 2018) - Qureshi, Mobeen; Liew, Ignatius; Bailey, Oliver
Abstract: Aim: We aim to assess post-operative CRP serum values in a cohort of patients who underwent surgical treatment for neck of femur fracture (NOF#), and whether CRP is a valid tool for the assessment of these patients post-operatively. Study Design and Methods: Retrospective analysis was carried out on all NOF#'s admitted for surgical fixation between August 2015 and July 2016 in a district general hospital. Primary analysis included serum CRP levels until day 7 post-operatively, with secondary analysis of any documented evidence of post-operative complications (medical and surgical) within 30 days post-operatively. Results: A total of 365 patients were surgically treated for NOF#'s over the study period. CRP serum levels peaked over the first two days post-operatively to median (IQ range) of 226 mg/L (158–299 mg/L), decreasing to 67 mg/L (45.5–104 mg/L) by day 7 post-operatively. 116 patients had documented post-operative complications within 30 daysof operation. CRP levels in patients with and without complications showed no statistical significance in day-1, day-2 and day-3 post-operatively. However, a significant difference was demonstrated on day-4 (p = 0.017), day-5 (p = 0.003), day-6 (p = 0.02) and day-7 (p = 0.031). Conclusions: During the first three days of the postoperative period we cannot recommend routine CRP serum blood test monitoring in NOF# patients, as it is not diagnostic in the acute inflammatory phase for medical or surgical complications.